2020
DOI: 10.1021/acs.oprd.0c00117
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Calorimetry in Continuous Flow Mode: A New Approach for the Thermal Characterization of High Energetic and Fast Reactions

Abstract: A new method for the calorimetric characterization of high-energetic, fast reactions in flow mode was developed. The use of an engineered flow reactor in combination with a process modeling software allowed the deconvolution of the reaction enthalpy from space-resolved temperature profiles. The new procedure was verified in a comparison with a conventional batch calorimeter and subsequently implemented for the thermal characterization of an organolithium flow process. The information collected for this reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 39 publications
(15 reference statements)
1
31
1
Order By: Relevance
“…Organometallic reactions and nitrations also fall into the category of type A reactions. Examples include the investigation of an organometallic reaction using flow calorimetry by Mortzfeld et al 19 and the nitration of phenol with concentrated HNO 3 as investigated by Glotz et al 22 Type B reactions, which are characterized by reaction halflives between 1 s and 10 min, are suitable for flow calorimetry only to a limited extent. Since in most cases microreactors are used for flow chemistry, a certain residence time is given by the reactors' internal volume and feeding rate of reactants.…”
Section: ■ Classification Of Calorimetersmentioning
confidence: 99%
See 1 more Smart Citation
“…Organometallic reactions and nitrations also fall into the category of type A reactions. Examples include the investigation of an organometallic reaction using flow calorimetry by Mortzfeld et al 19 and the nitration of phenol with concentrated HNO 3 as investigated by Glotz et al 22 Type B reactions, which are characterized by reaction halflives between 1 s and 10 min, are suitable for flow calorimetry only to a limited extent. Since in most cases microreactors are used for flow chemistry, a certain residence time is given by the reactors' internal volume and feeding rate of reactants.…”
Section: ■ Classification Of Calorimetersmentioning
confidence: 99%
“…The development of flow calorimeters is therefore of great interest for the design and operation of flow reactors. 19 In summary, the combination of microreactors and reaction calorimetry offers the following advantages:…”
Section: ■ Introductionmentioning
confidence: 99%
“…The closer this determination is to the industrial process, the more robust safety data are obtained. For example, Mortzfeld et al [7] found deviations in non-selective reactions when they were investigated using batch calorimeters or continuous flow calorimeters. Several flow calorimeters have been developed measuring the enthalpy of reaction using thermoelectric heat flow [8][9][10], infrared thermography [11], or segmental temperature sensors [7].…”
Section: Introductionmentioning
confidence: 99%
“…For the development of accurate kinetic models that assist chemical reactor development, design and optimization, extensive knowledge of interaction between reaction kinetics and hydrodynamics is essential [4]. Thus, the interest in the development of continuous flow calorimeter increases constantly [5][6][7][8]. Moreover, the miniaturization of calorimetry enables the investigation of fast and highly exothermic reactions under safe conditions due to the superior temperature control when compared to standard batch equipment [9].…”
Section: Introductionmentioning
confidence: 99%